Slums and prosperity: a complex, dynamic pathway of intervention. (15th July 2019) - Abubakar, Aisha; Romice, Ombretta; Salama, Ashraf M.
Abstract : Purpose: Slums have existed as long as cities have and are a growing context in the developing world. The challenge is in their efficient, effective and inclusive management. The purpose of this paper is to frame slums in the broad aim of urban development and the pursuit of prosperity, as active players and positive contributors in every right – a slum-prosperity framework. First, however, they need to be comprehensively defined in a non-exclusive, structured, dynamic and heuristic way; a previous publication was set to resolve this challenge. Design/methodology/approach: Guided by a synthesized operative model for prosperity, such a definition for slums is used to precisely relate their characters to the pursuit of prosperity through a mapping process, whereby these characters are linked to potentials for prosperity, improvement goals, resources and intervention plans. Findings: Both slums and prosperity are fuzzy, complex and variable terms; the only possibility to deal with them both is to break them down into simple and manageable yet operative units and establish the most influential and effective links between them to organize intervention according to patterns of change in both slums and city. Research limitations/implications: An intervention agenda like the one proposed here, that gives room for contextual and temporal urban complexities, has the potential to augment urban practice and help curb the slum phenomenon. A final paper (forthcoming) will illustrate the application of both the comprehensive definition of slum and the implementation of a pathway toward prosperity. Originality/value: The proposal in this paper is derived as part of research conducted for the award of a PhD at the University of Strathclyde Glasgow. This was in general set to contribute to the proactive and inclusive improvement of slums and cities. The proposal is further derived from the authors' involvement and personal interest in developing regions and is designed on local experience and on wider expertise in urban renewal.